EFEKTIVITAS MEDIA PEMBELAJARAN JANGKAR (JENGA KARTU AUGMENTED REALITY) TERINTEGRASI INDIGENOUS CULTURE DALAM MENINGKATKAN PEMAHAMAN KONSEP KEBERAGAMAN BUDAYA SISWA SEKOLAH DASAR - Chesta Briliant Nayottama, Orniga; Metalin Ika Puspita, Ari; Dellarosa, Maretha; Pandu Paksi, Hendrik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teaching about cultural diversity in the Pancasila Education course in elementary schools often faces challenges due to a lack of variety in the use of teaching materials, resulting in lessons that fail to provide concrete and meaningful learning experiences. This, in turn, leads to students’ suboptimal understanding of the concept of cultural diversity. This study aims to analyze the effectiveness of using JANGKAR (Jenga Augmented Reality Cards) media integrated with indigenous culture in enhancing elementary school students’ conceptual understanding of cultural diversity. The study employed a quantitative approach using a quasi-experimental design of the nonequivalent control group type. The research subjects consisted of 53 third-grade students at SDN Petemon XII/360 in Surabaya, with 27 students from Class III-A serving as the control group and 26 students from Class III-B as the experimental group. Data collection techniques utilized test instruments in the form of pretests and posttests, which were verified through Pearson Product Moment correlation validity and Cronbach’s Alpha reliability. The research data were analyzed using the Independent T-test, Cohen’s d effect size, and N-Gain. The results show that the independent t-test yielded a significance value of 0.040, indicating a significant difference between the test results of the experimental class and the control class. Additionally, the effect size test yielded a value of 0.5787, which falls into the moderate category, indicating a moderate effect of using the JANGKAR learning media integrated with indigenous culture. The N-Gain test yielded a value of 0.5859 or 58.59%, which falls into the moderate category, indicating that the media is quite effective. Thus, the JANGKAR (Jenga Augmented Reality Cards) learning media integrated with indigenous culture demonstrates sufficient effectiveness in improving students’ conceptual understanding of cultural diversity.